2017
DOI: 10.1111/1440-1681.12756
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of FSH signalling by CFTR and nuclear soluble adenylyl cyclase in the ovary

Abstract: Summary The cAMP/PKA pathway is one of the most important signalling pathways widely distributed in most eukaryotic cells. The activation of the canonical cAMP/PKA pathway depends on transmembrane adenylyl cyclase (tmAC). Recently, soluble adenylyl cyclase (sAC), which is activated by HCO3− or Ca2+, emerges to provide an alternative way to activate cAMP/PKA pathway with the cystic fibrosis transmembrane conductance regulator (CFTR), a cAMP‐activated Cl−/HCO3−‐conducting anion channel, as a key player. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 106 publications
(161 reference statements)
0
11
0
Order By: Relevance
“…Moreover, CFTR via the sAC-cAMP-PKA pathway has been shown to promote embryo development through the suppression of p53-dependent development arrest [ 93 ]. Taken together, the CFTR-sAC axis seems to play an important role in reproductive processes [ 94 ].…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 99%
“…Moreover, CFTR via the sAC-cAMP-PKA pathway has been shown to promote embryo development through the suppression of p53-dependent development arrest [ 93 ]. Taken together, the CFTR-sAC axis seems to play an important role in reproductive processes [ 94 ].…”
Section: Functional Role Of Sac In Different Cellular Compartmentsmentioning
confidence: 99%
“…59 At least in part, the JWXYS formula compounds interact with CYP19A1. The CDT network further indicates the JWXYS formula compounds could participate in modulating FSHR and LHCGR, therefore mimicking the endogenous FSH involved in stimulating the cAMP pathway in granulosa cells which then could regulate estrogen production, 60 through the link activation of CYP19A1-ESR1 ( Figure 4C). Another endocrine pathway shows that LH increases estradiol secretion in preantral follicles through up-regulating CYP17A1 and CYP19A1 gene transcripts in PCOS, 61,62 and reflect those two nodes observed in the CDT network.…”
Section: Discussionmentioning
confidence: 99%
“…According to population-based studies conducted in Taiwan, patients with uterine bleeding or hypertension received a JWXYS average daily dose of 7.3-7.5g. 37,38 Previous studies pointed out the indications JWXYS to be especially effective for alleviating menopausal symptoms and menstrual disorders. 33,39,[40][41][42] A clinical study indicated the use of JWXYS for improving depression status in menopause patients by increasing serum levels of TNF-alpha after 12weeks of treatment 43 and supported by a retrospective populationbased study that showed JWXYS as the most prescribed formula (12%) for patients having sleep disorders and major depressive disorder.…”
Section: Jia-wei-xiao-yao-san Formula Indicationsmentioning
confidence: 99%
“…Menopause contributes to osteoporosis and visceral adiposity, but management of these disorders has been challenging. Recent studies show that follicle‐stimulating hormone (FSH) signalling is amplified by cystic fibrosis transmembrane conductance regulator (CFTR) and nuclear soluble adenylyl cyclase in granulosa for the regulation of oestrogen production and granulosa cell proliferation (reviewed in Chen). Metabolic disorder in the CFTR/sAC pathway during amplifying other receptor‐activated cAMP/PKA signalling has been suggested to be involved in ovarian aging .…”
Section: Tissue‐specific Mechanisms Of Premature Aging and Diseasesmentioning
confidence: 99%
“…Recent studies show that follicle‐stimulating hormone (FSH) signalling is amplified by cystic fibrosis transmembrane conductance regulator (CFTR) and nuclear soluble adenylyl cyclase in granulosa for the regulation of oestrogen production and granulosa cell proliferation (reviewed in Chen). Metabolic disorder in the CFTR/sAC pathway during amplifying other receptor‐activated cAMP/PKA signalling has been suggested to be involved in ovarian aging . More recently, a polyclonal antibody targeting the beta‐subunit of the pituitary hormone FSH has been shown to increase bone mass and reduce adipose mass in mice .…”
Section: Tissue‐specific Mechanisms Of Premature Aging and Diseasesmentioning
confidence: 99%